Efektivitas Model Pembelajaran Berbasis Project (PBL) untuk Meningkatkan Kemampuan Berpikir Kritis Reflektif pada Mahasiswa - Aisyah; Mudhar; Hartanti, Jahju; Hasiana, Isabella; Firda Mufidah, Elia (FKIP Universitas Muhammadiyah Sukabumi, 2024)
This study aims to examine the effectiveness of the project-based learning (PBL) model in improving critical-reflective thinking skills in students. The PBL model was applied to two groups of students: an experimental group that followed project-based learning and a control group that followed conventional learning. This study used an experimental design with a pre-test and post-test to measure changes in critical-reflective thinking skills. Data were also collected through observation sheets and students' reflective journals. The results showed that the experimental group that applied the PBL model experienced a significant increase in critical-reflective thinking skills, with a significant difference in pre-test and post-test scores (p < 0.05). Meanwhile, the control group that followed conventional learning did not show a significant change. Analysis of the reflective journal showed that students in the experimental group were able to identify strengths and weaknesses in their thinking process, as well as evaluate the solutions they chose in the project. Based on these results, it can be concluded that project-based learning is effective in improving students' critical-reflective thinking skills, as well as encouraging active involvement and collaboration. This study recommends the use of the PBL model as an alternative to improving critical-reflective thinking skills in higher education.